2015
DOI: 10.1016/j.ejrh.2015.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of summer stream temperatures to climate variability and riparian reforestation strategies

Abstract: a b s t r a c tStudy region: The Salmon River is the second largest tributary of the Klamath River in northern California, USA. It is a region of steep mountains and diverse conifer forests. Historical land uses including logging, flow diversions, and hydraulic gold mining, have resulted in altered sediment transport regimes, diminished riparian cover and reduced large woody debris. These in turn have altered the thermal regime of the river. Summer stream temperatures commonly exceed salmonid (specifically Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
30
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 39 publications
3
30
0
1
Order By: Relevance
“…Moderate discharge conditions yield MWATs substantially cooler than low flows across most scenarios (Figure ), consistent with prior Heat Source modelling results (Bond et al, ). This suggests that maintaining minimum stream flows—especially during drought—could be an effective management strategy to maintain cooler stream temperatures and may be more important than reforestation.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Moderate discharge conditions yield MWATs substantially cooler than low flows across most scenarios (Figure ), consistent with prior Heat Source modelling results (Bond et al, ). This suggests that maintaining minimum stream flows—especially during drought—could be an effective management strategy to maintain cooler stream temperatures and may be more important than reforestation.…”
Section: Discussionsupporting
confidence: 88%
“…Changing incident solar radiation via reforestation has the greatest impact on AC stream temperatures, reflecting the minimal discharge and low thermal capacity there. Bond et al () generated similar Heat Source results, finding that the cooling effect of reforestation was substantially greater during low flow.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Some studies have already demonstrated observed declines in survival, population abundance, hybridization, and distribution shifts for cold‐water species (Bassar, Letcher, Nislow, & Whiteley, ; Isaak et al., ). Restoring riparian vegetation, especially in forested areas, may help to lessen climate change effects by shading streams from solar radiation and heat exchange (Battin et al., ; Bond, Stubblefield, & Van Kirk, ; Justice et al., ). Justice et al.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have already demonstrated observed declines in survival, population abundance, hybridization, and distribution shifts for cold-water species (Bassar, Letcher, Nislow, & Whiteley, 2016;Isaak et al, 2012). Restoring riparian vegetation, especially in forested areas, may help to lessen climate change effects by shading streams from solar radiation and heat exchange (Battin et al, 2007;Bond, Stubblefield, & Van Kirk, 2015;Justice et al, 2017). Justice et al (2017) demonstrated that riparian restoration may result in substantial water temperature reductions and increases in Chinook salmon populations in comparison to current conditions, even under scenarios of substantial warming.…”
Section: Introductionmentioning
confidence: 99%